2021
DOI: 10.1515/eng-2021-0110
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian fatality risk as a function of tram impact speed

Abstract: The objective of the presented research-work was to develop a model to describe the risk of fatal accident involving tram and pedestrian. This study extends research concerning relationships between the “impact speed” and probability of pedestrian death in case of tram accident. Over 400 “tram-pedestrian” accidents were analyzed. Logistic regression analysis was used in these studies. The main objective of the research is to compare the risk of fatal accidents when pedestrians are struck by passenger cars and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, injury severity for pedestrians is higher in tram-pedestrian accidents than in accidents with other motor vehicles. This particular higher injury risk has been documented in a number of studies, such as Hedelin et al, 2002;Margaritis, 2007;Naznin et al, 2016b;Chevalier et al, 2019, andGaca andFranek, 2021.…”
Section: Accident Datamentioning
confidence: 77%
See 2 more Smart Citations
“…However, injury severity for pedestrians is higher in tram-pedestrian accidents than in accidents with other motor vehicles. This particular higher injury risk has been documented in a number of studies, such as Hedelin et al, 2002;Margaritis, 2007;Naznin et al, 2016b;Chevalier et al, 2019, andGaca andFranek, 2021.…”
Section: Accident Datamentioning
confidence: 77%
“…The most serious injuries occur when pedestrians are run over (Hedelin et al, 1996). In general, the severity of tram-pedestrian accidents is primarily affected by vehicle related factors, especially by the mass difference between a tram and a human (a tram vehicle can weigh up to 50 tonnes) and ergonomics and stiffness of the vehicle's front (Hedelin et al, 1996;Grzebieta and Rechnitzer, 2000;Margaritis, 2007;COST, 2015;Gaca and Franek, 2021). A simulation study by Chevalier et al, 2019 on the effects on pedestrian injury by tram front-end shape, showed that the injury risk is more severe for the head than any other body region.…”
Section: Severity Of Tram-pedestrian Accidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedestrians face a higher risk of death when involved in tram collisions compared with automobile collisions at the same speed. Even at low impact speeds of 5-10 km/h, fatalities can occur due to the tram's front ergonomics, which lead to the full transfer of energy to the weak pedestrian body [6]. Therefore, it is necessary to investigate pedestrians' injuries in tram-pedestrian collisions.…”
Section: Introductionmentioning
confidence: 99%
“…The areas with the highest risk of tram-pedestrian collisions are public transport spots and pedestrian crossings [6]. Since tram drivers often operate their vehicles at low speeds due to caution, pedestrians may have a false sense of security and be unaware of the potential crash risk, resulting in risky situations [7].…”
Section: Introductionmentioning
confidence: 99%